Comparison of Wound Infection In Below Knee and Above Knee Vein Harvesting In Patients After Coronary Artery Bypass Grafting - Bangash, Tajamul Hussain; Muhammad Waseem; Janjua, Asif Mahmood; Ghouri, Muhammad Hashim; Nasir Ali; Muhammad Usama Akhtar; Tahseen Ahmed; Khan, Yasser (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare rate of wound infection between vein harvesting from thigh and leg among patients undergoing coronary artery bypass graft surgery (CABG). Study Design: Quasi-experimental study Place and Duration of Study: Cardiac Surgery Unit, Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi, Pakistan, from Jun 23 to Jan 24. Methods: Sample size was one hundred and sixty-nine. Patients were assessed for eligibility after informed consent and enrolled using a non-probability consecutive sampling technique. Both males and females above 40 years of age were included. Patients with diabetes, chronic kidney disease, redo cases, patients on steroids, and having any immunocompromised conditions, as well as pregnant women, were excluded. Patients were allocated into two groups i.e., Group-A (vein harvesting from thigh) and Group-B (vein harvesting from leg). After CABG, the wound was assessed using Southampton wound grading system (SWGS). Results: The study included one hundred and thirteen (66.86%) males and fifty-six (33.14%) females. Age ranged from forty five to seventy six years. Thirty-seven (21.89%) patients were smokers. Seven (4.14%) patients had surgery for single vessel coronary artery disease, twenty-five (14.79%) patients underwent surgery for double vessel coronary artery disease. Patients suffering from lesions of three coronary arteries constituted the highest number, one hundred thirty-seven (81.06%). Conclusion: Considering management of wound infection and available evidence in view, half-length vein harvesting should be done from leg.